Between tradition and modernity : aspects of Islam in South Asia - Maswood, Shireen; Dey, Amit, 1960-; Biswas, Ritwika; University of Calcutta. Department of History (Kolkata : K P Bagchi & Co., 2011)
Papers presented at a national seminar held at University of Calcutta in 2006.
Keywords: Islamic sociology -- South Asia -- Congresses; Islam and social problems -- South Asia -- Congresses; Bengali (South Asian people) -- Religion -- Congresses